2022
DOI: 10.3390/jcm11247276
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Diaphragmatic and Chest Wall Motion in People with Normal Pulmonary Function: A Study with Free-Breathing Dynamic MRI

Abstract: Objective: We aimed to quantitatively study the characteristic of diaphragm and chest wall motion using free-breathing dynamic magnetic resonance imaging (D-MRI) in Chinese people with normal lung function. Methods: 74 male subjects (mean age, 37 ± 11 years old) were prospectively enrolled, and they underwent high-resolution CT(HRCT), pulmonary functional tests (PFTs), and D-MRI in the same day. D-MRI was acquired with a gradient-echo sequence during the quiet and deep breathing. The motion of the diaphragm an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Our previous study on the effect of scoliotic spinal curves in TIS using dMRI showed a qualitative postoperative increase in the chest wall and diaphragmatic excursion. 4 Additionally, Yang X. et al 5 conducted a study on diaphragmatic motion in normal individuals using thoracic ratios and free-breathing dMRI. Their findings demonstrated a heightened prominence in the motions of the diaphragm apex and posterior diaphragm compared to the anterior diaphragm, supporting our observed trends.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study on the effect of scoliotic spinal curves in TIS using dMRI showed a qualitative postoperative increase in the chest wall and diaphragmatic excursion. 4 Additionally, Yang X. et al 5 conducted a study on diaphragmatic motion in normal individuals using thoracic ratios and free-breathing dMRI. Their findings demonstrated a heightened prominence in the motions of the diaphragm apex and posterior diaphragm compared to the anterior diaphragm, supporting our observed trends.…”
Section: Discussionmentioning
confidence: 99%
“…4 The normal diaphragm does not move uniformly during active breathing, with the greatest movement typically occurring in the middle and posterior third regions. 5 There is significant natural asymmetry between the morphological features and dynamics of normal right and left ventilatory volume components. 6 The right hemi-diaphragm (RHD) dome is positioned higher than the left hemi-diaphragm (LHD) during spontaneous breathing due to different mechanical properties of the diaphragm, phrenic nerve innervation, and the effect of the surrounding anatomical structures.…”
Section: Introductionmentioning
confidence: 99%
“…The height of the thorax was measured on the coronal cranial-caudal directions (CC) (Figure 3b and c) [11,18,19].…”
Section: Segmentation Of Mr Imagesmentioning
confidence: 99%
“…According to Yang et al [18], D-MRI was respectively obtained in one coronal, one right sagittal, and three transversal planes during free quiet-breathing and free deep-breathing with a breathing navigator to monitor the respiratory situation (Figure 2). The transversal images were respectively acquired at the level of the aortic arch, tracheal carina, and the right diaphragmatic dome which represent the upper, middle, and lower part of the chest wall (Supplement Figure 1).…”
Section: Mri Protocolmentioning
confidence: 99%
See 1 more Smart Citation